A Comparative Analysis of Superplasticizer Effects on the Flowability and Early Strength Development in Fly Ash Based Ultra High-Performance Concrete - Tajunnisa, Yuyun; Amalia, Aliif Rizki; Pratiwi, Wiwik Dwi (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study investigates the effects of different superplasticizer compositions on the performance of ultra high-performance concrete (UHPC). Superplasticizers enhance concrete's flow and reduce air content. This study compares two types of superplasticizers—naphthalene (SNF) and polycarboxylate (PCE)—at 1%, 1.5%, and 2% compositions. The research method involves material testing to determine the material characteristics and mix design, then explains the mixing, curing, and testing of various UHPC mixtures with various superplasticizers and compositions. Testing was conducted to evaluate the flowability and compressive strength at 1, 3, and 7 days. Results showed that PCE at 1.5% provided the best flowability (200 mm) and early strength (71.1 MPa at 7 days), whereas SNF yielded lower flowability (110 mm) and strength (39 MPa). The superior performance of PCE is attributed to its ability to disperse cement particles and accelerate hydration. The study concludes that the superplasticizer type and composition significantly impact UHPC's flowability and early strength.